Diagnostic Strategy and Treatment of Atypical Facial Lipoma: Case Report - Fernandes, Breno dos Reis; Bizzotto, Jéssica Fernanda; Weber Júnior, Volmir Ferreira; Abramsson, Adryleine Patrícia; Bortoloso, Alinne; Sant’Ana, Amanda Paino; Marchiori, Darah Lígia; Mulinari-Santos, Gabriel (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Lipoma is a benign tumor with slow growth. However, it is one of the most common tumors of soft tissues, its origin remains unclear. We present a case of a lipoma in the frontal region of the face, causing aesthetic and psychological discomfort to the patient. The strategy of treatment of this lesion is essential for a favorable prognosis.